Crack influence and fatigue life assessment in rail profiles: a numerical study - Urassa, Patrick; Habte, Haileleoul Sahle; Mohammedseid, Awel (Frontiers in Built Environment, 2023)
Rail transportation is a pivotal mode of land transport for its efficiency in transporting passengers and freight across short or long distances; hence the reliability and safety of rail systems are of key importance. Rolling contact fatigue (RCF), characterized by the cyclic loading of wheel-rail contacts, presents a significant challenge in the rail industry. This study presents a comprehensive numerical investigation on the influence of different crack orientations on the contact stress of the rail profile and subsequently the fatigue life. Using Finite Element Analysis (FEA) with Abaqus and FE-safe software, the study examines different crack orientations' impact on stress distribution and fatigue life of rail profiles. Employing the Extended Finite Element Method (XFEM), this study model cracks in rail profiles with different orientations; parallel, perpendicular, and oblique to the rail axis. FEA is used to obtain stress distribution results, highlighting the impact of crack presence, and orientation on maximum contact stresses. Subsequently, fatigue analysis is performed using FE-safe software, wherein the FEA results are imported to estimate fatigue life and damage evolution. The study reveals that the presence of a crack significantly influences the contact stress, fatigue life, and damage accumulation. The results further demonstrate that crack orientation has an impact on the severity of those effects. Oblique cracks exhibit higher impact compared to lateral and longitudinal cracks. The study provides valuable insights into rolling contact fatigue-related failures, aiding in better understanding and mitigation of such issues, thereby contributing to improved rail maintenance practices and system safety.